2008
DOI: 10.1007/s00421-008-0684-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-related physical fitness of adolescents and young adults with myelomeningocele

Abstract: To assess components of health-related physical Wtness in adolescents and young adults with myelomeningocele (MMC), and to study relations between aerobic capacity and other health-related physical Wtness components. This cross-sectional study included 50 adolescents and young adults with MMC, aged 16-30 years (25 males). Aerobic capacity was quantiWed by measuring peak oxygen uptake (peakVO 2 ) during a maximal exercise test on a cycle or arm ergometer depending on the main mode of ambulation. Muscle strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 41 publications
(52 reference statements)
1
38
0
1
Order By: Relevance
“…The identification of a group‐normalized WHEEL Scale RPE approximating the individualized Vpt provides a prescriptive reference on which to develop an exercise program that provides an overload aerobic exercise training stimulus. It is especially important that the SB population has a means of initiating, monitoring, and self‐regulating an aerobic exercise program throughout their lifespan due to generally poor health‐related aerobic fitness [33] and greater risk for obesity and obesity related conditions (eg, CVD, metabolic syndrome) that typify this population [6–8]. For instance, Buffart et al [8] found in young adults and adolescents with myelomeningocele, aerobic fitness was the only risk factor that showed a significant negative association with CVD risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of a group‐normalized WHEEL Scale RPE approximating the individualized Vpt provides a prescriptive reference on which to develop an exercise program that provides an overload aerobic exercise training stimulus. It is especially important that the SB population has a means of initiating, monitoring, and self‐regulating an aerobic exercise program throughout their lifespan due to generally poor health‐related aerobic fitness [33] and greater risk for obesity and obesity related conditions (eg, CVD, metabolic syndrome) that typify this population [6–8]. For instance, Buffart et al [8] found in young adults and adolescents with myelomeningocele, aerobic fitness was the only risk factor that showed a significant negative association with CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies involving people with clinical conditions that limit ambulation exclude wheelchair users. However, the SB population is comparatively less physically active and at greater risk for CVD and obesity as they age [6,14,33]. As such, fitness assessment and exercise prescription are valuable clinical adjuncts to treating individuals with SB who are primary wheelchair users.…”
Section: Discussionmentioning
confidence: 99%
“…Movement duration is the accumulation of the amount of a certain intensity exercise. For the development of physical fitness, only to achieve a certain amount of exercise intensity of the accumulation of time is effective [3][4][5][6].…”
Section: Methodsmentioning
confidence: 99%
“…Zusätzlich müssen Muskel-und Koordinationstraining intensiver erfolgen [19,38], da diese vor allem bei hohen Lähmungen frakturprophylaktisch wirken. Ob die Elektrotherapie einen unterstützenden Effekt auf die Muskelkraft hat, ist aufgrund der Datenlage nicht zu beantworten [39].…”
Section: Trainingunclassified